Sintering of cobalt and strontium doped lanthanum chromite obtained by combustion synthesis - Setz, L. F G; Corrêa, H. P S [UNESP]; Paiva-Santos, C. O. [UNESP]; Mello-Castanho, S. R H (Trans Tech Publications, 2006)
Lanthanum chromite (LaCrO3) is one of the most adequate materials for use as interconnector in solid oxide fuel cell (SOFC) applications, due to its intrinsic properties, namely its good electrical conductivity and resistance to environment conditions in fuel cell operations. Due to difficulties in sintering, additives are usually added to help in the densification process. In this work, the influence of added cobalt and strontium, in the sintering of LaCrO3 obtained by combustion synthesis was studied. The starting materials were respectively nitrates of chromium, lanthanum, cobalt and strontium, and urea was used as fuel. The results show that by increasing the strontium and cobalt concentrations it is possible to reduce the temperature of sintering. Using both additives, the sintering processes took place in lesser times than normally used for this material, as well as greater values of density were attained.
Keywords: Combustion synthesis; Fuel cell; Lanthanum chromite; Sintering; Electrical conductivity; Interconnectors; Intrinsic properties; Densification; Solid oxide fuel cells (SOFC); Lanthanum compounds